2011
DOI: 10.1088/0953-8984/23/26/265004
|View full text |Cite
|
Sign up to set email alerts
|

First-principles atomistic study of surfaces of Fe-rich Fe–Cr

Abstract: The surface properties of Fe-rich ferromagnetic Fe-Cr alloys are investigated using a first-principles quantum-mechanical method. In dilute alloys, the surfaces are dominated by Fe, whereas the Cr-containing surfaces become favorable when the bulk Cr concentration exceeds the limit of ∼ 10 atomic per cent. The abrupt change in the surface behavior is the consequence of complex competing magneto-chemical interactions between the alloying atoms. Considering the quantities of various features: equilibrium surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…We notice that both the bulk enthalpy of formation and the surface segregation phenomena in Fe-Cr have been discussed using some of these alternative methods [19,29,31,32], and a comparison with the EMTO-CPA predictions demonstrates the validity of our approach.…”
Section: A First-principles Calculationsmentioning
confidence: 76%
See 2 more Smart Citations
“…We notice that both the bulk enthalpy of formation and the surface segregation phenomena in Fe-Cr have been discussed using some of these alternative methods [19,29,31,32], and a comparison with the EMTO-CPA predictions demonstrates the validity of our approach.…”
Section: A First-principles Calculationsmentioning
confidence: 76%
“…However, in Cr-rich Fe-Cr alloys the antiparallel coupling of the Cr moments with the Fe matrix inevitably leads to parallel coupling between the moments of the chromium atoms leading to an increase in energy with increasing Cr content. The effects of the magnetic configuration on the total energy of the Fe-Cr alloy and the atomic magnetic moments in the four topmost atomic layers and in the bulk have been calculated and discussed in our previous investigation [29]. It has been shown that this kind of magnetic frustration has a key role in the miscibility of the Fe-Cr alloys [17].…”
Section: A Initial Relaxation In the Surface Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Fe-Cr alloys the situation seems to be more complex. It turns out that, in spite of the large surface magnetic effects (Aldén et al, 1992(Aldén et al, , 1994Vitos et al, 1998), the surface energy of pure Cr is significantly (~ 30%) larger than the one calculated for pure Fe (1.41 eV per surface Fe atom) (Ropo et al, 2011;Ropo et al, 2007), thus preventing Cr atoms going to the surface. The surface energy difference between the pure Fe-and pure Cr-terminated surfaces is even larger (~36%) in Fe-rich Fe-Cr alloys.…”
Section: Surface Propertiesmentioning
confidence: 80%
“…When compared to the surface ECP, one can see that the crossover between the bulk and surface chemical potentials is indeed a consequence of the rapidly rising (convex) mixing enthalpy. On these grounds (Badini & Laurella, 2001;Götlind, Liu, Svensson, Halvarsson, & Johansson, 2007;Klaver et al, 2006), we can conclude that the magnetism-driven solubility of Cr in Fe is in fact the main factor responsible for the increasing stability of Cr containing surfaces compared to Fe-terminated surfaces (Ropo et al, 2011).…”
Section: Surface Propertiesmentioning
confidence: 83%